Meta-analysis of factors related to health services that predict treatment default by tuberculosis patients Metanálise de fatores relacionados aos serviços de saúde que predizem o abandono de tratamento por pacientes com tuberculose - Pedro Emmanuel Alvarenga Americano do Brasil; José Ueleres Braga (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
The identification of factors that predict tuberculosis (TB) treatment default can help control this problem. The current study used a systematic review to investigate associations between TB treatment default and previously studied factors related to health services. Abstracts were searched in the MEDLINE and LILACS databases and in the bibliography of the full texts under evaluation. Studies were included if TB treatment default was evaluated by comparing two or more groups and data could be extracted. A total of 41 studies were included for combining data. It was possible to combine five exposures: "difficult access to health services"; "need for hospitalization"; "training or support for adherence"; "delay in initiating treatment"; "long wait before medical attendance". "Difficult access to health services", "training or support for adherence", and "need for hospitalization" were associated with TB treatment default. All exposures demonstrated heterogeneity, which was only explained in one. Publication bias was only detected for one exposure. Acredita-se que a identificação dos fatores que são preditores do abandono de tratamento de tuberculose contribuiria para o seu controle. Este trabalho combinou, por meio de uma revisão sistemática, medidas de associação entre abandono do tratamento de tuberculose e de fatores relacionados com os serviços de saúde já estudados. Resumos foram procurados nas bases LILACS e MEDLINE e na bibliografia dos textos completos em avaliação. Foram incluídos estudos nos quais foi avaliado o abandono do tratamento através de comparações de dois ou mais grupos e nos quais foi possível a extração de dados. Ao final, 41 investigações foram incluídas para combinação de dados. Foi possível combinar cinco exposições: "difícil acesso aos serviços de saúde"; "necessidade de hospitalização"; "treinamento ou suporte para adesão"; "demora para o início do tratamento" e "espera longa antes da consulta". "Difícil acesso aos serviços de saúde", "treinamento para adesão" e "necessidade de hospitalização" demonstraram associação com o abandono de tratamento de tuberculose. Todas as exposições apresentaram heterogeneidade e em apenas uma esta foi explicada. Viés de publicação foi encontrado em apenas uma exposição.